MEMBACA AL-QUR’AN DENGAN HATI YANG TERPADU: Studi Kritis atas Hadis Riwayat Muslim dari Jundab bin Abdullah al-Bajali - Muhammad Aji Nugroho (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2015)
The source of conflict within Muslim community is notcoming from Qur’an, but from its reader. The situation is contributingto rising conflict within every Muslims that believed Qur’an asguidance (huda), explanation (bayyinat), and distinguishing (furqon).Those conflicts should be terminated through going back to theQur’an as form of confirmation (tabayyun), not confrontation(tafarraqu, taba’adu, and tanaza’u), in order that Muslimcommunities have not avoiding the plurality of their realities and thatrequisite conflict and controversy. Thereby the study making sense tothe reader because Hadits believed as the second source of Islamiclaw after the Qur’an which is functioned as bayan tafsr, bayan taqrir,and bayan tasyri’ of the Qur’an, giving instruction to stay away fromthe Qur’an when the disagreement (ḥilafiyat) emerged. In order toknow the Hadis could be used as hujjah or not, the study covered:takhrij al-hadis, i’tibar as-sanad, naqd as-sanad (critic of sanad),naqd al-matn (critic of matan).